Energy Efficient Transceiver Design for NOMA VLC Downlinks with Finite-Alphabet Inputs - Wang, Zhen-Yu; Yu, Hong-Yi; Wang, Da-Ming (Applied sciences, 2018)
Non-orthogonal multiple access (NOMA) is considered as a promising technique in visible light communication (VLC) systems for performance enhancement. In order to improve the system’s energy efficiency, we carry out transceiver design for an NOMA VLC system. We develop an optimal power allocation scheme for the system based on finite-alphabet inputs, and we propose a joint detection and decoding (JDD) algorithm for signal detection. Comprehensive simulation results demonstrate that our proposed NOMA strategy can achieve significant performance gains over the time division multiple access (TDMA) scheme, and our designed JDD algorithm outperforms the conventional successive interference cancellation (SIC) algorithm for NOMA.